PENGARUH PERHATIAN ORANG TUA TERHADAP MINAT BELAJAR SISWA JURUSAN AKUNTANSI - Sibarani, Blasius Erik (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
The problem in this study is the low interest in learning in class X accounting majors at SMK Negeri 2 Balige due to low parental attention. The purpose of this study was to determine the effect of parental attention on the interest in learning of class X students in the Accounting Department at SMK Negeri 2 Balige. This research was conducted at SMK Negeri 2 Balige. The population in this study were all 107 students of class X Accounting Department at SMK Negeri 2 Balige. The sampling technique is total sampling so that the number of samples used is 107 respondents. The data obtained were analyzed using the PLS (Partial Least Square) analysis technique through SmartPLS software. The data collection technique in this study was in the form of a questionnaire. The data obtained were analyzed using the PLS Algorithm test, PLS Bootstrapping and hypothesis testing using the t-test. The results of the analysis obtained that the average reflected is above 0.5 and the outer loading indicator is higher than 0.6. The data from the calculation for the research hypothesis where parental attention affects students' learning interest is obtained from the p-value of 0.000 while the real level or is 0.05. Thus, it can be concluded that parental attention has an effect on students' interest in learning.